2020
DOI: 10.1021/acs.analchem.9b04410
|View full text |Cite
|
Sign up to set email alerts
|

Light-Up Lipid Droplets Dynamic Behaviors Using a Red-Emitting Fluorogenic Probe

Abstract: Intracellular lipid metabolism occurs in lipid droplets (LDs), which is critical to the survival of cells. Imaging LDs is an intuitive way to understand their physiology in live cells. However, this is limited by the availability of specific probes that can properly visualize LDs in vivo. Here, an LDs-specific red-emitting probe is proposed to address this need, which is not merely with an ultrahigh signal-to-noise (S/N) ratio and a large Stokes shift (up to 214 nm) but also with superior resistance to photobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 48 publications
0
65
0
1
Order By: Relevance
“…[1] While it has been reported that the ripening process can last from af ew minutes to several hours in adipocytes and nematodes, [28] it is challenging to trace LD coalescence because it is unpredictable,a nd is considered ar are phenomenon with only af ew reports dedicated to studying the process. [29] In an attempt to observe the coalescence event using our system, we stained HeLa cells using LD-FG and performed SIM imaging.A ss hown in Figure 5b,i tw as observed that ac luster of LDs experienced 5c oalescence events in 1min with most processes lasting less than 2s(Movie S4). We also observed the formation of an intermediate morphology during LD coalescence.A sshown in Figure 5b from 48 st o 54 s, two adjacent LDs changed from two distinct circles and fused to form as ingle dumbbell-shaped entity,w hich equilibrates to form as ingular distinct larger circular LD.D uring coalescence,itwas observed that the fluorescence intensity of fused LDs increased, which indicates ah igher neutral lipid density after coalescence.I na ddition, LD coalescence was also observed to occur in other cellular regions (Figures S13,S14).…”
Section: Ld Dynamics Imaging:fusion Interactions With Organelles and Turnovermentioning
confidence: 99%
“…[1] While it has been reported that the ripening process can last from af ew minutes to several hours in adipocytes and nematodes, [28] it is challenging to trace LD coalescence because it is unpredictable,a nd is considered ar are phenomenon with only af ew reports dedicated to studying the process. [29] In an attempt to observe the coalescence event using our system, we stained HeLa cells using LD-FG and performed SIM imaging.A ss hown in Figure 5b,i tw as observed that ac luster of LDs experienced 5c oalescence events in 1min with most processes lasting less than 2s(Movie S4). We also observed the formation of an intermediate morphology during LD coalescence.A sshown in Figure 5b from 48 st o 54 s, two adjacent LDs changed from two distinct circles and fused to form as ingle dumbbell-shaped entity,w hich equilibrates to form as ingular distinct larger circular LD.D uring coalescence,itwas observed that the fluorescence intensity of fused LDs increased, which indicates ah igher neutral lipid density after coalescence.I na ddition, LD coalescence was also observed to occur in other cellular regions (Figures S13,S14).…”
Section: Ld Dynamics Imaging:fusion Interactions With Organelles and Turnovermentioning
confidence: 99%
“…Recent studies showed that hydrophobic dyes with high logP (n-octanol/water partition coefficient) value are inclined to locate in lipid droplets (Zhao et al, 2019 ; Wang L. et al, 2020 ; Ye et al, 2020 ; Zhang F. et al, 2020 ; Zhang X. et al, 2020 ). A few fluorescent dyes have been applied for two-photon lipid droplet imaging in live cells and fixed tissues (Collot et al, 2018 ; Fam et al, 2018 ).…”
Section: Bioimaging Applicationsmentioning
confidence: 99%
“…[1][2][3][4][5][6] During the past decade, the cell biology of LDs has been a focus of intensive research. It has become clear that LDs are dynamic organelles, integral to cell metabolism, with a fascinating cycle of biogenesis, [7][8][9] consumption, [10] and highly associated with obesity, [11] diabetes, [12,13] inflammatory disorders, [14][15][16] and cancer. [17,18] The traditional imaging techniques, such as Raman microscopy, transmission electron microscopy, and immunofluorescence microscopy, [19][20][21] have been employed for the purpose to visualize lipid droplets, but some challenges have still been existed, such as complicated procedures and poor cellular permeability and thus may disturb the functions of cells.…”
Section: Introductionmentioning
confidence: 99%